Antibacterial activity of honey against beta-lactamase resistant E.coli. - Bearneza, Bethany (UPHSI, 2015)
This study aimed to determine the effectiveness of the different concentrations of honey against Escherichia coli (E. coli) beta-lactamese resistant bacteria. Kirby-Bauer Disc Diffusion Method was strictly followed in the experiment with six concentrations of nine replicates each. The concentrations of honey used are 10 mL pure concentration for 100%, 2.5 mL water and 7.5 mL honey for 75%, 5 mL water and 5 mL honey for 50%, 7.5 mL water and 2.5 mL honey for 25% and 10 mL of water for negative control. Honey concentrations were measured using a graduated cylinder, mixed, stirred, and stored inside the test tubes in room temperature. Ciprofloxacin was used as the positive control. After 24 hours of incubation at 37 degrees celcius, zones of inhibition were observed and measured. It was only the Ciprofloxacin (positive control) that exhibited the higest mean zone of inhibition while all the different concentrations of honey exhibited no zone of inhibition. Results show the honey is not effective as antibacterial agent against E. coli beta-lactamase bacteria.